Defects Affecting the Qurban: A Study of Islamic Law Perspectives - Abdualhmeed Alqahoom (Demak Universal Journal of Islam and Sharia, 2023)
Discussing the issue of legal disputes in the defects in the qurban is an attempt to remove it from the barriers to acceptance because it is rituals that show the integrity of the purpose, and the cleansing of his intentions in terms of worship. These rituals have been going on for only one year, this is also evidence of the reality of sharia and its tolerance, this study aims to study the defects that affect sacrifice by explaining its laws. These defects prevent the acceptance of worship, so the purpose of this study is to be a guide for Muslims in sacrificial worship and to be accepted in the sight of Allah. This research is an inductive and qualitative model, with normative, theological, and fiqh approaches. The results of the study concluded that there are some basic and legal differences, and it is done to save the perpetrators of sacrificial worship, to be safer and more accepted worship. إن ذكر الخلاف الفقهي في عيوب الأضحية سعي لاستخلاصها من الموانع الحاجبة لقبولها، إذ هي شعيرة عظمية من الشعائر الدالة على سلامة مقصد، وخلوص نيته في قربانه، وإن كان هذه الشعيرة سنة فهو دليل على واقعية الشريعة وسماحتها، فيهدف البحث في دراسة العيوب المؤثرة في الأضحية ببيان حكمها، العيوب المانعة من قبولها، لتكون دليلًا للمسلم في توجيه نسكه، وصحة تعبده وتقربه إلى ربه، فسلكت فيها المنهج الاستقرائي، وخلصت أن الاختلاف في اختلاف تنوع، فهي تخرجها عن وصف السلامة لا القبول